Hands-on reinforcement learning for games implementing self-learning agents in games using artificial intelligence techniques - Lanham, Micheal (Packt Publishing, 2020)
The AI revolution is here and it is embracing games. Game developers are being challenged to enlist cutting edge AI as part of their games. In this book, you will look at the journey of building capable AI using reinforcement learning algorithms and techniques. You will learn to solve complex tasks and build next-generation games using a ...